2023
DOI: 10.1111/jwas.13003
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion effect of jack mackerel,Trachurus japonicus, meal in the diet of rockfish,Sebastes schlegeli, on growth, feed utilization, biochemical composition, and innate immune responses

Abstract: Dietary inclusion effects of various levels of jack mackerel meal (JMM) on growth, feed utilization, biochemical composition, and innate immune response of rockfish were determined. The control (Con) diet included 550 g/kg fish meal (FM). Ten, 30, 50, 100, 200, 400, 600, and 1000 g/kg of JMM were included in the Con diet, referred to as the JMM10, JMM30, JMM50, JMM100, JMM200, JMM400, JMM600, and JMM1000 diets, respectively. Eight hundred and ten fish (initial mean weight of 2.3 g) were distributed into 27 flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…However, no statistical differences in growth, SGR, and feed intake of rockfish which were fed the C20J60 and C20J80 diets implied that the C20J60 diet appeared to be the most recommended dietary treatment in this experiment. However, incorporated JMM levels up to 40% in the 55% FM-based diet improved weight gain, SGR, and feed intake of rockfish; however, JMM inclusion levels higher than 40% (60% and 100%) did not improve further when juvenile rockfish were fed with a 55% FM-based diet or one of the diets which include 1, 3, 5, 10, 20, 40, 60, and 100% JMM at the cost of FM in the 56-day feeding experiment [19]. They also concluded that optimum inclusion levels of JMM were estimated to be 39.7 and 40.3% based on weight gain and feed consumption, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, no statistical differences in growth, SGR, and feed intake of rockfish which were fed the C20J60 and C20J80 diets implied that the C20J60 diet appeared to be the most recommended dietary treatment in this experiment. However, incorporated JMM levels up to 40% in the 55% FM-based diet improved weight gain, SGR, and feed intake of rockfish; however, JMM inclusion levels higher than 40% (60% and 100%) did not improve further when juvenile rockfish were fed with a 55% FM-based diet or one of the diets which include 1, 3, 5, 10, 20, 40, 60, and 100% JMM at the cost of FM in the 56-day feeding experiment [19]. They also concluded that optimum inclusion levels of JMM were estimated to be 39.7 and 40.3% based on weight gain and feed consumption, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…However, their attractiveness to fish varies greatly depending on fish species, feeding patterns, and the type and dosage of attractants [14,17]. Some feed ingredients in formulated fish feeds, such as tuna viscera hydrolysates and jack mackerel (Trachurus japonicas) meal (JMM), could improve feed intake [13,[17][18][19]. In particular, Chotikachinda et al [13] unveiled that the inclusion of 3-4% tuna viscera hydrolysates in the 54% poultry by-product meal-based diet enhanced feed palatability and increased the feed consumption and growth of Asian sea bass.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, 21.5% of wheat flour and 4.5% of each fish and soybean oils were contained as carbohydrate and lipid sources in the Con diet, respectively. In the Con diet, 25% and 50% FM were substituted with CGM, SPC, and CPC, respectively, and then 22% JMM, achieving the best growth and highest feed consumption of rockfish (Kim and Cho, 2023), was added at the sacrifice of FM in all plant-substituted diets, named as the CGM25, CGM50, SPC25, SPC50, CPC25, and CPC50 diets, respectively. All experimental feeds met the dietary protein and lipid requirements of rockfish (Cho et al, 2015).…”
Section: Experimental Design and Feedsmentioning
confidence: 99%